Day 3 Wed, November 11, 2020 2020
DOI: 10.2118/202641-ms
|View full text |Cite
|
Sign up to set email alerts
|

Novel Technology to Improve Recovery of Remaining Oil in Tight Glutenite Reservoir of Junggar Basin: Employing Chemical Diverting Agents in Refracturing Operation

Abstract: The production wells in tight glutenite reservoirs have great potential for refracturing, because most of fracturing fluid and proppant flow into the first-class layer with lower initiation pressure during initial stimulation with multi-layer simultaneous fracturing treatment. However, layer segmentation during refracturing can be a challenge, especially in vertical wells. Using only mechanical segmentation tools is of high risk and sometimes ineffective. This paper presents a new refracturing technology for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Initially, the pipeline is filled with approximately 500 mL under a constant pressure of 1 MPa, followed by injection at a constant rate of 200 mL/min until a pressure drop occurs and cannot be re-pressured, indicating successful fracturing. Studies have shown that a combination of differentparticle-size temporary plugging agents can effectively increase the sealing pressure [23][24][25][26]. Therefore, the IFTP and ISTP stages use variable-viscosity slickwater with a viscosity of 5 mPa•s, which is supplemented with a combination of small-particle-size plugging agents (80-120 mesh + 20-80 mesh) and large-particle-size plugging agents (1-2 mm + 1-3 mm), respectively.…”
Section: Experimental Parametersmentioning
confidence: 99%
“…Initially, the pipeline is filled with approximately 500 mL under a constant pressure of 1 MPa, followed by injection at a constant rate of 200 mL/min until a pressure drop occurs and cannot be re-pressured, indicating successful fracturing. Studies have shown that a combination of differentparticle-size temporary plugging agents can effectively increase the sealing pressure [23][24][25][26]. Therefore, the IFTP and ISTP stages use variable-viscosity slickwater with a viscosity of 5 mPa•s, which is supplemented with a combination of small-particle-size plugging agents (80-120 mesh + 20-80 mesh) and large-particle-size plugging agents (1-2 mm + 1-3 mm), respectively.…”
Section: Experimental Parametersmentioning
confidence: 99%
“…Temporary plugging agents composed of different particle size are often sent to plug the fracture near the well and promote the fracture diversion in the fracturing process, since the temporary plugging efficiency of multi-particle size combined temporary plugging agents are better than that of single particle size temporary plugging agents [30][31][32][33]. Four groups of rock specimens were designed for comparative experiments in order to study the influence of different particle size combinations of temporary plugging agents on the fracture propagation geometry in temporary plugging fracturing, respectively, 1#, 2#, 3#, and 4#.…”
Section: The Influence Of Particle Size Combinationmentioning
confidence: 99%